Infrared Radiation in the Thermosphere From 2002 to 2023 - Martin G. Mlynczak; Linda Hunt; Nabil Nowak; B. Thomas Marshall; Christopher J. Mertens (Geophysical Research Letters)
Abstract Twenty‐two years (2002–2023) of infrared radiative cooling rate data derived from the SABER instrument on the NASA TIMED satellite are presented. Global daily and global annual infrared power (Watts, W) emitted by nitric oxide (NO) and carbon dioxide (CO2) illustrate the variability of the geospace environment on timescales from days to decades. The 11‐year solar cycle (SC) is evident in the global power data and in vertical profiles of infrared cooling rates (nW/m3). The global annual power radiated by NO and CO2 are larger in 2023 than at any time since 2003 and 2002, respectively. The to‐date peak in NO infrared power in SC 25 is larger than in SC 24, is comparable to SC 20, but is less than in SCs 18–19 and 21–23. Two geomagnetic storms in 2023 radiated more than 1 TW and are in the top 10 strongest storms observed by SABER.